Impact of health education-based intervention on community’s awareness on dengue and its prevention in Chidambaram during COVID-19 pandemic - N., Rama Swathika; T.K., Senthil Murugan (International Journal Of Community Medicine And Public Health, 2022)
Background: Dengue fever is a global public health issue. It is acknowledged that vast, repeated, intense, and persistent health education programs for community mobilization are essential to achieving the aforementioned goals. The main objective of the study was to increase the dengue-related awareness and behavioral change through health education-based intervention among the selected urban communities in Chidambaram. Methods: A quasi experimental, community-based interventional study conducted among 150 residents of urban area of Annamalai Nagar, Chidambaram district consisting of both males and females of age groups between 18-75 years who were selected using stratified random sampling technique. Data was collected using semi structured questionnaire before and after intervention using flipchart, entered in Microsoft Excel and analysed using SPSS software. Descriptive and analytical statistics were applied. Results: Most of the study participants (32.7%) were in the age group of 30-39 years. More women (68.7%) participated in the survey among which 50.7% were educated up to secondary and higher secondary class. On comparing the results of mean values of knowledge, attitude and practice between pre-test and post-test, reflected significant improvement upon after health education by flipchart intervention. It was found very highly significant (p<0.001) between mean knowledge scores and significant (p<0.05) between mean practice scores. Conclusions: Health education could contribute to changes in perceptions, social capital, and a healthy house condition. It is very important to increase the awareness and participation of the community in controlling dengue prevalence.